Optimizing Career Choices in the World of Programming: A Web-Based Decision Support System with the Simple Additive Weighting (SAW) Method - Akbar, Mohammad Arsan; Rusli, Risvan; Wahid, Yokogeri Abdullah; Surianto, Dewi Fatmarani; Adiba, Fathiah (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
This study proposes the development of a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to help students choose a career in programming. By integrating data from online questionnaire surveys and observations, this research highlights the complexity of career choice in the world of programming. Criteria such as salary, work location, and educational requirements were identified as key factors in decision-making. The SAW method was chosen because of its ease of understanding, flexibility, and ability to handle complex problems. The system implementation process involves data collection, observation, web-based system design, and website development. The final results show that alternative A3 (Software development) received the highest preference weight, confirming it as the best choice based on the specified criteria. The use of DSS is expected to provide effective guidance for students in making more informed career decisions.